2007
DOI: 10.1088/0957-4484/18/27/275708
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube integrated multifunctional multiscale composites

Abstract: Carbon nanotubes (CNTs) demonstrate extraordinary properties and show great promise in enhancing out-of-plane properties of traditional polymer composites and enabling functionality, but current manufacturing challenges hinder the realization of their potential. This paper presents a method to fabricate multifunctional multiscale composites through an effective infiltration-based vacuum-assisted resin transfer moulding (VARTM) process. Multi-walled carbon nanotubes (MWNTs) were infused through and between glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
160
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(166 citation statements)
references
References 42 publications
(31 reference statements)
6
160
0
Order By: Relevance
“…This combination of properties makes these materials particularly attractive for many applications in aerospace [1], automotive [2] and the 0008-6223/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved. doi:10.1016/j.carbon.2011.03.011 energy sector, both in alternative energy, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination of properties makes these materials particularly attractive for many applications in aerospace [1], automotive [2] and the 0008-6223/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved. doi:10.1016/j.carbon.2011.03.011 energy sector, both in alternative energy, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned techniques to develop ''multiscale'' materials have been explored primarily for carbon fiber-reinforced composites, and only a few studies have been reported on the effect of adding CNTs to glass fiber-reinforced composites [8,[12][13][14][15][16]. It should also be noted that, to date, most of the literature related to these composites refers to thermoset matrices, which are usually prepared by direct infusion of the CNT/polymer resin into the glass fabric through vacuum-assisted resin transfer molding (VARTM) [17] method.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the result, it can be seen that GO significantly obstructs the epoxy curing reaction, leading to positive effect on molecular chain mobility. The less restriction on molecular chain mobility grounds to decrease the T g [35,36].…”
Section: Characterization Of Graphene Oxide/epoxy Nanocompositesmentioning
confidence: 99%
“…Several researches have been reported on impregnation of CNTs into carbon fibers (CFs): infusion/impregnation of a CNT-resin mixture into the primary fiber assembly [8,9], direct growth of CNTs on reinforcement fiber surface through chemical vapor deposition (CVD) [10,11], direct placement of CNTs between layers of the preform [12], electrophoretic deposition onto the surface of fiber [13,14], electrostatic assembly of oxidized CNTs onto functionalized fiber [15] and coating of fiber with CNT-containing sizings [16][17][18][19][20]. Especially, the first and the third methods are widely used due to the easiness of application.…”
Section: Introductionmentioning
confidence: 99%